A Comparative Analysis of the Gene Expression Profiles of Small Cell Esophageal Carcinoma, Small Cell Lung Cancer, and Esophageal Adeno/Squamous Carcinoma - Liu, Di; Wen, Junmiao; Chen, Jiayan; Wang, Boyan; Xu, Xinyan; Zhang, Zhen; Fan, Min (Frontiers in Surgery, 2021)
Purpose/Objectives: This study investigated the gene expression profile of small cell esophageal carcinoma (SCEC) and compared it with the expression profiles of small cell lung cancer (SCLC) and esophageal adeno/squamous carcinoma (EAC/ESCC).Materials/Methods: All patients with SCEC, SCLC, and EAC/ESCC in the Surveillance, Epidemiology, and End Results (SEER) database 1973-2014 were included. Overall survival (OS) and prognostic analysis were conducted. De novo expression array analysis was performed on three pairs of frozen primary SCEC tissues and corresponding normal samples from the institutional tissue bank using the Affymetrix HG U133 plus 2.0 array. These data were complemented with public domain expression data sets from the GEO repository using the same working platforms, which included primary SCLC, EAC/ESCC and normal lung/esophagus specimens (series GSE30219, GSE26886). After individual normalization, the primary tumors were submitted to statistical analysis (GeneSpring GX 13.0) to identify the differentially expressed genes (DEGs) relative to their paired normal tissues. Enrichments of genes categorized by function and gene interactions were analyzed by DAVID 6.8 and STRING 11.0, respectively.Results: The clinical outcome of the SCEC patients were significantly more worse than those with EAC/ESCC and SCLC in the SEER database. SCEC had more DEGs in common with SCLC than EAC/ESCC, leading to a stronger correlation between SCEC and SCLC (Pearson’s correlation coefficient was 0.60 for SCEC vs. SCLC, 0.51 or 0.45 for SCEC vs. ESCC or EAC). Similar findings were obtained by principal component analysis using all DEGs retrieved from these four groups. Functional annotation showed that a higher proportion of pathways and biological processes were common between SCEC and SCLC and were associated with the cell cycle, DNA replication, telomere maintenance, DNA repair, P53 and RB pathways (Benjamini p <0.05). Compared with EAC/ESCC, SCEC shared more co-up-regulated DEGs coding for the aforementioned common pathways with SCLC (584 vs. 155). In addition, SCEC and SCLC were found to have possessed overlapping gene interactive networks, with CENPF, NEK2, KIF11, TMPO, and FOXM1 as common skeletons centered by NUF2.Conclusion: Our preliminary data indicate that SCEC and SCLC display notably similar patterns of gene expression for mitosis and DNA repair. Further validation studies are warranted